Pelagic copepod diversity (Crustacea: Copepoda) in the southern Caribbean: evidence of a pending assignment - Joxmer Scott-Frías; Fernando Cervigón; Evelyn Zoppi de Roa; Eduardo Suárez-Morales (Revista Mexicana de Biodiversidad)
The Southern Caribbean (SCA) represents the most productive ecoregion of the Tropical Northwestern Atlantic (TNWA) province. In order to assess the diversity of pelagic copepods in the ecoregion, we present an inventory based on unpublished data obtained from several oceanographic cruises made in oceanic and neritic waters of Venezuela (1967-1968). We complement this information with previous regional surveys to obtain a revised systematic checklist of the pelagic copepod species in the SCA. We included in our list a total of 346 species and 2 subspecies; up to 11 species represent new records. This study allowed us to: 1) expand the distributional range of some species within the TNWA, 2) record the occurrence, in the SCA, of all species known to 12 of 42 families to occur in the TNWA, 3) determine that the number of species of Corycaeidae and Paracalanidae in the SCA is greater than previously documented for the TNWA. Overall, the species accumulation curve resulting from our data analysis allowed us to determine that the diversity of pelagic copepods is underestimated; our estimations suggest that the potential species number that can be recorded in the SCA is 12 to 48% above the figure herein established.